2013
DOI: 10.1002/ajmg.b.32169
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic transmission and complex neuro developmental network for attention deficit hyperactivity disorder: Genome‐wide association study of both common and rare variants

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a complex polygenic disorder. This study aimed to discover common and rare DNA variants associated with ADHD in a large homogeneous Han Chinese ADHD case–control sample. The sample comprised 1,040 cases and 963 controls. All cases met DSM-IV ADHD diagnostic criteria. We used the Affymetrix6.0 array to assay both single nucleotide polymorphisms (SNPs) and copy number variants (CNVs). Genome-wide association analyses were performed using PLINK. SNP-heritability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 37 publications
9
156
1
Order By: Relevance
“…The genome-wide significance threshold was calculated by considering the three ADHD clinical subtypes and was set at Po1.7e À 08 (5e À 08/3). The phenotypic variance explained by all autosomal SNPs for ADHD was calculated with GCTA software (Yang et al, 2013). The gene-based association analysis was performed with the VEGAS software following the default settings and considering the HaMap CEU samples to estimate the linkage disequilibrium (LD) structure (Liu et al, 2010 Carlson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genome-wide significance threshold was calculated by considering the three ADHD clinical subtypes and was set at Po1.7e À 08 (5e À 08/3). The phenotypic variance explained by all autosomal SNPs for ADHD was calculated with GCTA software (Yang et al, 2013). The gene-based association analysis was performed with the VEGAS software following the default settings and considering the HaMap CEU samples to estimate the linkage disequilibrium (LD) structure (Liu et al, 2010 Carlson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This situation, along with advances in high-throughput technologies, stimulated a turn towards genome-wide association studies (GWAS). To date, GWAS of ADHD have been completed in seven independent datasets, six of which used pediatric samples (Franke et al, 2009;Hinney et al, 2011;Lesch et al, 2008;Mick et al, 2010;Neale et al, 2008;Neale et al, 2010a;Stergiakouli et al, 2012;Yang et al, 2013). None of them reported genome-wide significant associations and, apart from the possible involvement of cadherin 13 (CDH13) identified in three reports (Lesch et al, 2008;Neale et al, 2008;Neale et al, 2010a), there is limited overlap between them or with previous linkage or candidate gene association studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain imaging studies have identified alterations in both gray matter and white matter in the brain in patients with ADHD (Thapar and Cooper, 2015). Findings from recent genetic studies also support the involvement of white matter alterations in ADHD, as genes involved in neuronal migration, axonal guidance, and myelination have been repeatedly found amongst the tophits in hypothesis-free, genome-wide gene-finding studies (Poelmans et al, 2011;Thapar and Cooper, 2015;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Common genetic factors with small effects sizes, rare variations with larger effect sizes (such as copy number variations [CNVs]) and very rare chromosomal anomalies, with even bigger effect sizes, contribute to the disorder in the population (2,134) (Fig. 3).…”
Section: Molecular Geneticsmentioning
confidence: 99%